Resiliency Among Various Businesses in the Philippines in the Context of Post-Disaster Recovery Framework - Cutillas, Anesito L.; Alburo, Rosalyn P.; Alburo, Hemres M.; Pascual, Pet Roey L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This research highlights the aspects of resiliency among business establishments in the Visayas regions that were directly affected by super typhoon Yolanda in 2013. This study employs a descriptive method to characterize resiliency factors among various businesses. A survey questionnaire was utilized to gather relevant data from the 106 business proprietors and managers. Multivariate analysis via exploratory factor analysis (EFA) was used to determine the underlying factors. In the context of the post-disaster recovery of businesses in the Visayas regions, the exploratory analysis yielded five dimensions. Based on the finding, five causal factors are significant in developing a post-disaster resiliency and recovery framework among various business types. Any business is considered resilient against any form of disaster if it has complete control of its institutional affairs and plans ahead guided by its philosophy. Futuristic planning is also necessary as it imbibes in its operational philosophy the value of foresight. Besides, every business needs to strengthen its linkages outside its operations. Hence, a resilient business considers the value of information exchange and dissemination. Thus, a business is said to be sustainable if it maintains a sound and working framework to improve an adaptive capacity for any calamity or disaster.